2020
DOI: 10.1128/iai.00315-20
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Chlamydial Pathogenicity by Nonspecific CD8+T Lymphocytes

Abstract: Chlamydia trachomatis, a leading infectious cause of tubal infertility, induces upper genital tract pathology such as hydrosalpinx, which can be modeled with Chlamydia muridarum infection in mice. Following C. muridarum inoculation, wild type mice develop robust hydrosalpinx but OT1 mice fail to do so because their T cell receptors are engineered to recognize a single ovalbumin epitope (OVA457-462). These observations have demonstrated a critical role of Chlamydia-specific T cells in chlamydial pathogenicity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Moreover, repletion of TNF-α +/+ CD8 + T cells in CD8 gene deficient mice restores the pathology comparable to wild type animals (Murthy et al 2011 ). Consistently, Guangming et al (Xie et al 2020 ) demonstrated that CD8 + T cells from OT1 mice also significantly inhibited hydrosalpinx development in wild-type mice following an intravaginal inoculation with Chlamydia. They conclude the hydrosalpinx-inhibitory CD8 + T cells are Chlamydia nonspecific or independent of chlamydial antigen recognition.…”
Section: Discussionmentioning
confidence: 63%
“…Moreover, repletion of TNF-α +/+ CD8 + T cells in CD8 gene deficient mice restores the pathology comparable to wild type animals (Murthy et al 2011 ). Consistently, Guangming et al (Xie et al 2020 ) demonstrated that CD8 + T cells from OT1 mice also significantly inhibited hydrosalpinx development in wild-type mice following an intravaginal inoculation with Chlamydia. They conclude the hydrosalpinx-inhibitory CD8 + T cells are Chlamydia nonspecific or independent of chlamydial antigen recognition.…”
Section: Discussionmentioning
confidence: 63%